Effect of Different Beverages on Intraocular Pressure - Asad Ullah, Maryam Jabbar, Muhammad Siddique, Naseer Fatima, Amna, Sehresh Parveen, (Pakistan Journal of Medical & Health Sciences, 2023)
Purpose: Young individuals regularly consume a wide range of drinks with caffeine content. In this study, healthy young subjects' intraocular pressure (IOP) was evaluated in relation to energy drinks, tea,coffee and water. Methodology: A prospective longitudinal, multi-centered study was conducted from March 2022 to August 2022. Data was collected through non-probability consecutive sampling technique. A total of 100 subjects of both genders (male and female) age ranging between 15 to 30 years were included. A thorough ophthalmic examination was required for subjects to satisfy a set of study protocol, that included not suffering any ocular diseases, intraocular pressure of 10-20 mmHg, absence of systemic diseases. Exclusion criteria included patient who had undergone anterior and posterior segment ophthalmic surgeries. The participants were randomized into four groups at random. Each group comprises of 25 subjects. IOP was measured before as baseline and after 60 min of intake. SPSS was used for data analysis. Results: Out of 100 subjects 77 were female and 33 were male. The first group consumed tea, the second group coffee, the third group energy drinks, and the fourth group water. Baseline IOP on average in each group water, tea, coffee and energy drink intake was 15.58 ± 1.79, 15.49 ± 1.87, 15.23 ± 1.05, 15.68 ± 1.32 respectively. While IOP was 14.89±2.01, 15.01 ± 1.23, 15.67±1.98 and 16.01 ± 2.33 after 60 minutes of consuming water, tea, coffee, and energy drinks. IOP fluctuations between before and after consuming water, tea, coffee, and energy drinks were 0.69, 0.48, -0.75, and -1.29. Practical Implication: This study has important clinical implications since it may help people realise they should limit their intake of certain beverages in order to lower their intraocular pressure (IOP). No research on the impact of beverages on intraocular pressure (IOP) has been done in Pakistan, as far as we are aware. This led to the formulation of the current investigation. Conclusion: Two groups demonstrated an increase in IOP, whereas the IOP in the other two groups declined. Compared to tea consumption, which has a modest quantity of caffeine, consuming coffee and energy drinks raises intraocular pressure. This study suggested avoidance of coffee and energy drinks intake should be emphasized prior to IOP measurement to avoid any potential error. Keywords: intraocular pressure, beverages, energy drinks, tea, coffee, water